Rehabilitation Intervention to Restore the Functionality of the Shoulder With Scapular Fracture - Case Report - H.A. Burileanu; M. Zavaleanu; G. Ionescu; I. Burileanu; L. Brabiescu Calinescu (Editura Universitatii Transilvania din Brasov, 2023)
This report presents an individualized physical therapy program and the therapeutic results for a 36-year-old man with a posttraumatic left scapular body fracture with minimal displacement and without ribs fractures scapular fracture. Because the glenoid fossa was intact, conservative treatment was recommended. The patient reports arm activities dysfunctions. The rehabilitation was conducted in an outpatient physical therapy clinic from Craiova under direct supervision for 12 weeks. At the end of the follow-up period, the level of pain was considerably decreased. Despite the functional deficit from the beginning of the rehabilitation program, normal function was restored. The patient was fully involved and cooperative during the physical therapy session.